Environment and Nitrogen Rate Play Significant Roles in Winter Wheat Response to Nitrogen Management Intensification - L. M. Simão; D. A. Ruiz Diaz; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2022)
Poor nitrogen (N) management is among the leading causes of winter wheat (Triticum aestivumL.) yield gaps in Kansas, and sowing date—which is impacted by crop rotation—is among the most important variables determining winter wheat’s attainable yields in the U.S. central Great Plains. This research aimed to investigate the relationship between N management strategies and various cropping systems in Kansas. The treatments consisted of nine combinations of three N management practices (standard, progressive, and green N) and five crop sequences (WtWt = continuous winter wheat; SyWt = winter wheat after soybean; TrSyWt = triticale (hay) – soybean – winter wheat rotation; CpWt = winter wheat after cowpea; TpDPwt = dual-purpose winter wheat after tepary bean; MoDPwt = dual-purpose winter wheat after moth bean). Standard N-management consisted of one single broadcast N application at 80 lb/a as UAN at spring greenup. Progressive N-management consisted of a split-N application at 40 and 27 lb/a each at greenup and jointing, using streamer bar nozzles and N-inhibitors added to the fertilizer. Green N management consisted of no fertilizer application except for the carryover N from the previous terminated legume crop. Crop sequences that allowed winter wheat to be sown at the optimum sowing date had the greatest yields. Green N management decreased dual-purpose winter wheat grain yield and shoot biomass. Both standard and progressive N management practices had similar results within crop sequences. Overall, our results suggested that intensive N management produced the same yields as the standard, but at lower N rates. Dual-purpose winter wheat combined with green N (i.e., relying exclusively on carryover N) was detrimental to winter wheat yield.
Keywords: nitrogen stabilizer; nitrogen timing; nitrogen rate; nitrogen source; 4R; Triticum aestivum L.